The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijerph20064768
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical Lineage and Evolutionary Logic of Research on the Environmental Behavior of Family Firms: A Literature Review

Abstract: Family firms research is becoming one of the most important and promising areas for theoretical innovation in management practice. Corporate environmental behavior has attracted widespread academic attention, but the research on the environmental behavior of family firms is obviously insufficient, and the relevant research results are still in a fragmented state. In this paper, we review and summarize the existing research on the environmental behavior of family firms from three aspects: the research dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Conversely, beyond an optimum level of family ownership (52,2% of the share capital), uncertain future financial returns of innovation investments may jeopardize SEW preservation in the long run (Chrisman and Patel, 2012). The concern for financial sustainability and the desire to preserve family wealth for future generations (Geng et al, 2023) make family companies less prone to invest in risky activities (Mitter et al, 2014) to the detriment of environmental performance. According to literature, board diversity may influence environmental performance via structural as well as demographic characteristics (Garc ıa Mart ın and Herrero, 2020; Orazalin and Mahmood, 2021;Islam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, beyond an optimum level of family ownership (52,2% of the share capital), uncertain future financial returns of innovation investments may jeopardize SEW preservation in the long run (Chrisman and Patel, 2012). The concern for financial sustainability and the desire to preserve family wealth for future generations (Geng et al, 2023) make family companies less prone to invest in risky activities (Mitter et al, 2014) to the detriment of environmental performance. According to literature, board diversity may influence environmental performance via structural as well as demographic characteristics (Garc ıa Mart ın and Herrero, 2020; Orazalin and Mahmood, 2021;Islam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Improving employee health is one of the critical concerns of firms (Hilsdorf et al, 2017). Moreover, firms seek to minimise the risks that are associated with employees by identifying environmental issues that present a challenge to the health and safety of employees (Chen et al, 2022;Geng et al, 2023;Han & Huo, 2020;Suharti & Sugiarto, 2020) and mitigate them to create a healthy working environment for them (Gouda & Saranga, 2020). Further, Li et al (2023) and Gu (2023) found that EP reduces health benefit costs by improving the employees' health.…”
Section: Ep and Ehomentioning
confidence: 99%
“…Environmental Behaviors (EB) have long been considered an important ethical issue (Collado et al, 2019). Currently, human environmental behaviors are recognized as one of the most in uential factors in the environment (Geng et al, 2023). Similarly, employees' behavior is considered the main factor in the successful adaptation of organizations to the environment (Blasco-Giner et al, 2023).…”
Section: Introductionmentioning
confidence: 99%